Physiological selectivity of insecticides to two lacewing species - Godoy, Maurício Sekiguchi; Carvalho, Geraldo Andrade; Carvalho, Beatriz Ferreira; Lasmar, Olinto (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the effects of insecticides recently released for the control of citrus pests on adult specimens of Chrysoperla externa and Ceraeochrysa cubana. The products used and their respective dosages in g L-1 of a.i. were: thiametoxam 200 WG, 0.05; imidacloprid 700 WG, 0.07; milbemectin 50 CE, 0.008; pyriproxyfen 100 CE, 0.075; and spirodiclofen 240 SC, 0.06. In each treatment, 11 couples of C. externa and 13 of C. cubana, at an age up to 24 hours, were submitted to the application of the insecticides and water (control), through a Potter´s tower. Adults mortality and oviposition capacity were evaluated in a period of eight weeks, as well as the viability of laid eggs. Thiametoxam was classified as harmful to C. externa; imidacloprid as moderately harmful and the other insecticides as harmless. As for C. cubana, thiametoxam was considered harmful; spirodiclofen was slightly harmful and the other products were innocuous. The insecticides milbemectin, pyriproxyfen and spirodiclofen can be recommended to integrated pest management programs aiming at the maintenance of these species of beneficial arthropods in citrus areas.